Neural basis of human aggression: a systematic review of biologically based approaches to aggression from 2010 to 2024 - VOLYNETS, Volodymyr (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
Background. Given the current realities in Ukraine, particularly the war and the escalating societal tensions, the importance of studying aggression cannot be overstated. However, when examining this phenomenon, it is crucial to avoid oversimplification and seek deeper explanations that account for its multifaceted nature. Generally, there are several explanations for aggression: the genetic explanation, which posits that aggression is influenced by the perinatal effects of genes and their polymorphisms, or their expression through phylogenetic influences; the hormonal explanation, which analyzes aggression through the mechanisms of specific neurotransmission process; and the neuroanatomical explanation, which examines aggression based on the functioning of particular brain areas. The aim of the study was to analyze research conducted over the past 15 years and to provide a comprehensive overview of the factors involved in the development of aggressive behavior by describing various concepts pertaining to its emergence. Methods. In line with the objective of thoroughly covering recent research on diverse mechanisms of aggression, methods of abstraction and information synthesis were employed in the literature analysis. The findings are organized into separate structural elements following a clear framework, starting from perinatal development and work of general neurotransmitter systems to the specific functions of individual brain areas. Results. This study consolidates and structures information from different approaches to the aggression studies. It describes the genetic, hormonal, and neuroanatomical determinants of aggression. The influence of various systems on aggressive behavior is emphasized, whether it is pathological or non-pathological in nature. Conclusions. The challenge of studying aggression as a unified phenomenon stems from the inadequacies of its research mechanisms and the frequent contradictory conclusions regarding the same manifestations. This complicates addressing the root causes of aggression and improving societal psychological well-being. Nevertheless, emphasizing the diversity of its nature and promoting diverse research directions, especially considering varying environments and the imperfections in brain system functions, offers hope for developing targeted methods to address the complex system of aggression. The foundational study of aggression holds promise for furthering a comprehensive theory of aggression that investigates various studies into a cohesive discourse.